Recruitment, growth patterns, and longevity of the deep-water velvet shrimp Metapenaeopsis sibogae (De Man, 1907) (Decapoda: Dendrobranchiata: Penaeidae). Issue 5 (23rd August 2018) - Rahman, Md Mosaddequr; Ohtomi, Jun
Abstract: We studied for the first time the recruitment, growth patterns, and longevity of Metapenaeopsis sibogae (De Man, 1907 ) using length-frequency method from monthly samples obtained from January 2013 to December 2014. We compared the von Bertalanffy growth function (VBGF) and the Pauly and Gaschütz growth function to the mean length-at-age data to identify any seasonal oscillation in growth rate and to suggest the best-fit model for describing growth. A single, short pulse of recruits of both sexes was observed from January to April, which was probably synchronized with the main spawning season with a time-lag of 3–4 months. Sexual dimorphism related to body size was found with the highest amplitude of body size recorded for females. We detected almost no seasonality in growth rate. The VBGF was adopted as the best fitting model to describe the growth of both sexes. The estimated equations were Lt = 16.79 [1 – exp – 0.181 (t + 0.867)] and Lt = 19.56 [1 – exp – 0.139 (t + 1.928)] for males and females, respectively. Growth differed significantly between the sexes. Longevity was estimated to be 27 months for males and 28 months for females. The relationship between carapace length and body weight showed negative allometric growth for both sexes.